Moderate accumulation of calcium and phosphorus in the splenic artery with aging and low accumulation of those in the pulmonary artery with aging - Iria Maria Prieto Payo (2018)
To elucidate compositional changes of the arteries with aging, the authors investigated age-related changes of elements in the splenic and pulmonary arteries, which supplied blood to contractile organs. After ordinary dissection by medical students at Nara Medical University was finished, the splenic and pulmonary arteries were resected from the subjects, ranging in age from 58 to 94 years. The element contents were determined by inductively coupled plasma-atomic emission spectrometry. It was found that a moderate accumulation of Ca and P occurred in the splenic artery with aging, but it hardly occurred in the pulmonary artery with aging. Regarding the relationship among elements, the finding that there were significant direct correlations among the contents of Ca, P, Mg, and Na was commonly obtained in both the splenic and pulmonary arteries. The accumulation of Ca and P in the splenic artery with aging occurred independently of that in the pulmonary artery. Histologic observation indicated that a major part of Ca deposits was seen in the middle tunica, but not in the internal tunica. Therefore, the calcification occurring in the splenic artery belonged to middle sclerosis. © Humana Press Inc. 2007.